2019
DOI: 10.6061/clinics/2019/e989
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology for the treatment of deep endometriosis: uptake of lipid core nanoparticles by LDL receptors in endometriotic foci

Abstract: OBJECTIVE: Rapidly dividing cells in multiple types of cancer and inflammatory diseases undergo high low density lipoprotein (LDL) uptake for membrane synthesis, and coupling an LDL-like nanoemulsion, containing lipid nanoparticles (LDE) to a chemotherapeutic agent efficiently targets these cells without significant systemic effects. This was a prospective exploratory study that evaluated the uptake of a radioactively labeled LDE emulsion by receptors of endometriotic foci and the capacity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…quantified the uptake of lipid nanoparticles in endometriotic lesions of affected patients scheduled for surgical intervention. [ 47 ] One day before surgery, patients were intravenously administered 0.1 mL of solid cholesterol lipid core nanoparticles containing cholesterol [ 14 C]‐oleate. Following resection and biopsy, 14 C in endometrial, peritoneal, and endometriotic tissues were evaluated using liquid scintillation spectrometry.…”
Section: Accumulation Of Nanoparticles In Endometriosis Lesionsmentioning
confidence: 99%
“…quantified the uptake of lipid nanoparticles in endometriotic lesions of affected patients scheduled for surgical intervention. [ 47 ] One day before surgery, patients were intravenously administered 0.1 mL of solid cholesterol lipid core nanoparticles containing cholesterol [ 14 C]‐oleate. Following resection and biopsy, 14 C in endometrial, peritoneal, and endometriotic tissues were evaluated using liquid scintillation spectrometry.…”
Section: Accumulation Of Nanoparticles In Endometriosis Lesionsmentioning
confidence: 99%
“…For example, a number of investigators have proposed the role of lipoproteins in the promotion of cancer progression [ 44 ]. And LDL is the largest cholesterol transporter of the body [ 45 ]. The LDL receptor on tumor cells is overexpressed to meet the high demand of cholesterol which is necessary for the rapid cell proliferation and de novo membrane synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Bedin et al showed preliminary results in which they found a high uptake of labelled LDE by the topical endometrium, which can be used as a nanosystem. 104 Another mechanism of endometriosis that can be studied regard the autophagy process, in which Beclin-1 play an essential positive regulatory role. 105 Zhao et al devised a hyaluronic acid (HA) (PEI-SA/ DNA) as a tool for Beclin-1 gene delivery and consequent Beclin-1 upregulation within endometrial lesions.…”
Section: Emerging Therapeutic and Theranostic Nanotechnology Approach...mentioning
confidence: 99%